EVALUASI HARGA SEWA PASAR BARU MARABAHAN TIMUR DITINJAU DARI SEGI FINANSIAL PROYEK - Maulana Rifki Ramadhani; Irfan Prasetia (Jurnal Teknologi Berkelanjutan, 2020)
Barito Kuala District Government has built the east Marabahan New Market, to reduce the number of street vendors (PKL) that are increasingly prevalent in the city of Marabahan. Because this project is a government project that tend to prioritize social benefits that can be provided to the community, it is necessary to do the feasibility study of the east Marabahan new market in terms of financial investment. This study aims to determine the rent price of the new market based on the considerations used for the operational and maintenance costs of the east Marabahan new market building. The financial project analysis methods used are the Payback period method, the Net Present value (NPV) method, the Internal Rate of Return (IRR) method, and the Benefit Cost Ratio method. Based on calculations with an investment cost of Rp. 5,635,397,000.00 and an interest rate (BI rate) of 6% over the life of the building, a rental fee can be obtained for each kiosk. The results of the financial calculation at a price of Rp. 189,000, - indicates a positive NPV value, the IRR is greater than the interest rate set and the BCR is more than 1. Thus, the rental price at east Marabahan new market is feasible to apply. Calculation results are also supported by the results of a price questionnaire to the public. Where the results show 64% agree with the price of Rp. 189.000,-.